The role of cladocerans in green and brown food web coupling - Urbano,Vinicius de A. (2022)
ABSTRACT Cladocerans, an important zooplankton community, are consumers from the base of the food web of aquatic environments. We investigated the contribution of producers (phytoplankton and periphytic biofilm) and particulate organic carbon (POC). Collections were carried out in lakes of the Upper Paraná River Floodplain, the last stretch free of dams in the second-largest South American basin. Isotope ratios (δ13C and δ15N) were measured, besides the contributions of probable food sources to the cladocerans biomass. The phytoplankton constituted the source of carbon for cladocerans, followed by POC. Thus this work, in addition to emphasizing the importance of cladocerans in nutrient cycling, highlighted the need for the conservation of environments surrounding the lakes as they are the sources of organic matter for aquatic communities. Besides, the analyzed zooplanktonic organisms demonstrated their role in the interconnection between the green and brown food webs, which have been studied separately for a long time.